Analysis of circulating tumor cells in patients with multiple myeloma during the course of high-dose therapy with peripheral blood stem cell transplantation - Kiel, Katja; Cremer, Friedrich Walter; Rottenburger, Christof; Kallmeyer, Charlotte; Ehrbrecht, Edith; Atzberger, A.; Hegenbart, Ute; Goldschmidt, Hartmut; Moos, Marion (Bone marrow transplantation, 1999)
In multiple myeloma (MM) circulating CD19+ cells have been considered as myeloma precursors. As these cells are also possibly a reservoir of treatment resistant disease evaluation of the CD19+ cells during the course of high-dose therapy has to be a major concern. We determined the number of tumor cells in the CD19+ as well as CD19− fractions of PB of eight patients with disease sensitive to VA[I]D chemotherapy, of 10 patients who achieved partial or complete remission post-high-dose therapy (HDT) with peripheral blood stem cell transplantation (PBSCT) and of a further seven patients with disease progression post-transplantation. CD19+ cell fractions were obtained by preparative sequential magnetic and fluorescence activated cell sorting with a median purity of 97.1%. In addition, PB samples of seven patients post-transplantation were sorted for CD20+cells (median purity, 98.7%). The number of tumor cells in the CD19+, the CD19− and the CD20+ fractions were determined using a quantitative CDR3 PCR assay. The number of CD19+ tumor cells in patients in remission post-HDT was similar to those of the patients post-VA[I]D (median, 1.05 vs 0.92 CD19+ tumor cells/ml PB, P = 0.72) providing evidence for the persistence of this tumor cell fraction during the course of HDT. This was in contrast to the CD19−compartment, in which the number of tumor cells was significantly reduced in those patients in remission post-transplantation (median, 53 vs 0 CD19− tumor cells/ml PB; P= 0.006). In patients with progressive disease the number of tumor cells in both cell fractions was significantly higher (CD19+: median, 1.05 vs 21 tumor cells/ml PB, P = 0.05; CD19−: 0 vs 63 tumor cells/ml PB, P = 0.008). While the absolute number of CD19+ cells was reduced in the group of patients after VA[I]D treatment, a polyclonal CD19+ reconstitution had occurred in patients responding to HDT. The tumor cell content in the CD19+ fractions could be confirmed by the results obtained analyzing the CD20+ cell fractions. In conclusion, these results indicate that disease progression after PBSCT in MM is accompanied by an expansion of tumor cells in both the CD19+ and CD19− fractions. Similar numbers of CD19+ clonotypic cells post-HDT suggest that these cells persist and thus, contribute to disease dissemination and relapse.
Gesehen am 01.03.2022